Reflecting on "A Statistician in Medicine" in 2020. (23rd December 2020) - Dempsey, Walter; Mukherjee, Bhramar
Abstract : In this commentary, we revisit Sir Austin Bradford Hill's seminal Alfred Watson Memorial Lecture in 1962 through the eyes of two practicing biostatisticians of the current era. We summarize some eternal takeaway messages from Hill's lecture regarding observations and experiments translated through the modern lexicon of causal inference. Finally, we pose a series of questions that we would have liked to pose to Sir Austin Bradford Hill if he were to deliver the lecture in 2020.